STRATEGI HUMAS POLSEK CIMENYAN DALAM MENSOSIALISASIKAN TINDAK KRIMINAL DI WILAYAH CIMENYAN - ROCKY HARYONO (Jurnal Komunikasi dan Bisnis, 2020)
This research was conducted to explain the strategy carried out by the Cimenyan Police Public Relations in disseminating information about criminal acts that occurred in the Cimenyan area. With the rampant crime in the city of Bandung, especially when there was a Covid outbreak that occurred in Indonesia, then the need for strategies to strive for, minimize the occurrence of crime, especially in this Cimenyan region, by conducting socialization to the surrounding communities around crime and its dangers and how to overcome it . The research method used is a qualitative research method with a descriptive approach. Data collection techniques are carried out through interviews and observations, including by interviewing the Public Relations Police of Cimenyan Sector and members related to the title discussed, as well as making observations by jumping directly into the field. The strategy carried out by the Cimenyan Police Public Relations is with a persuasive, educative and informative strategy. The results obtained are the strategies carried out by the Cimenyan Police Public Relation went well, and were well received by the community and were very effective. Keywords: Public Relations Strategy, Socialization, and crime.